PETIKAN DAWAI GITAR DI TENGAH PANDEMI COVID-19: INKLUSI KEUANGAN UMKM - Saifudin, Saifudin; Safitri, Ulfa Nur; Widowati, Sri Yuni (Fakultas Ekonomi, Universitas Semarang, 2022)
The purpose of this study was to determine the financial management of MSMEs during the Covid-19 pandemic. This research was conducted at the GRBK UMKM in Kadilangu Village, Trangkil District, Pati Regency.This type of research uses a qualitative case study method, with data collection using in-depth interview techniques, direct observation and documentation. Testing the credibility of the data using the data source triangulation technique and the data triangulation technique. The informants in in-depth interviews were as many as 3 (three) participants who were considered to understand, understand and master information related to the problems that occurred in the study.The results of this study indicate that the financial management of GRBK MSMEs during the Covid-19 pandemic applies financial management by implementing 4 indicators, namely the use of the budget, recording, reporting, and controlling. The company's financial performance is in good condition. Financial management is carried out independently by the owner with manual but routine record. However, it is not in accordance with the accounting regulated in SAK ETAP. SAK EMKM is due to the lack of financial literacy and inclusion for GRBK business owners.